Psychomotor Skills of Pre-service Teachers of Natural Science on Melde’s Experiment in Guided Inquiry Learning - Septi Budi Sartika; Noly Shofiyah (IJORER : International Journal of Recent Educational Research, 2020)
This research aimed to describe the psychomotor skills of pre-service teachers of natural science on Melde’s Experiment through guided inquiry learning. Psychomotor skills were assessed by observation during students conduct the Melde’ s experiment. This research method used was descriptive quantitative in which the authors described the research variables from the collected data. The study was conducted on a pre-service natural science teacher who learns the Optic and Geometry Course. The data analysis uses descriptive statistical. The results showed that the psychomotor skills of pre-service teachers of natural science are categorized as very good in manipulation, good in precision and articulation; fair in imitation and naturalization domain. The lowest category of psychomotor indicators is naturalization. Naturalization is doing related activities according to the skills that are owned, a sample designing experiment with different variables. Different variables with the module make the prospective teacher’s students think hard to create the experimental draft, consequently, the experimental design and findings are not equal to the theory. Further research is expected to have a learning model that is capable of training better psychomotor skills.